A weak mixed mobile ion effect in vanadium-tellurite oxide glass modified by silver and lithium cations - Cardillo, Evangelina Cinthia (2010)
The effect of the partial replacement of lithium oxide by silver oxide in a glassy vanadium-molybdenum-tellurite oxides matrix is analyzed by means of impedance spectroscopy. We find that a weak mixed mobile ion effect (MMIE) is due to the different kind of modifications silver and lithium oxides induce in the glass of formula 0.7[x Ag2O (1 - x) Li2O] 0.3[0.5 V2O5 0.5 MoO3] 2 TeO2.